2016
DOI: 10.1038/srep25891
|View full text |Cite
|
Sign up to set email alerts
|

Crumpling Damaged Graphene

Abstract: Through molecular mechanics we find that non-covalent interactions modify the fractality of crumpled damaged graphene. Pristine graphene membranes are damaged by adding random vacancies and carbon-hydrogen bonds. Crumpled membranes exhibit a fractal dimension of 2.71 ± 0.02 when all interactions between carbon atoms are considered, and 2.30 ± 0.05 when non-covalent interactions are suppressed. The transition between these two values, obtained by switching on/off the non-covalent interactions of equilibrium con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
5
14
0
Order By: Relevance
“…It was shown that (i) disorder can crumple a membrane in agreement with Ref. [31] and (ii) instability of the rippled phase predicted in Refs. [29,30] develops logarithmically slow, i.e., the marginal T = 0 rippled phase controls elastic properties of disordered freestanding graphene for T = 0 in a wide interval of length scales (see also Ref.…”
Section: Critical Elasticity Of Membranessupporting
confidence: 83%
See 3 more Smart Citations
“…It was shown that (i) disorder can crumple a membrane in agreement with Ref. [31] and (ii) instability of the rippled phase predicted in Refs. [29,30] develops logarithmically slow, i.e., the marginal T = 0 rippled phase controls elastic properties of disordered freestanding graphene for T = 0 in a wide interval of length scales (see also Ref.…”
Section: Critical Elasticity Of Membranessupporting
confidence: 83%
“…In graphene, κ 0 ∼ 1 eV, so that the thermal fluctuations alone are not enough to crumple it. At the same time, recent numerical simulations of disordered graphene clearly indicate the crumpling transition [31]. Additional evidence for the importance of disorder in graphene is provided by recent experimental measurements of anomalous Hooke's law [32,33].…”
Section: Critical Elasticity Of Membranesmentioning
confidence: 84%
See 2 more Smart Citations
“…A good review on the subject can be found in [2]. The most important examples for the less-known models are also the BTW sandpile model [10][11][12], the watersheds [13], the graphene system [14,15], the normal state of the YBCO superconducting planes [16], the random field Ising model [17], the Ising model on the * morteza.nattagh@gmail.com percolation systems [18], the (2 + 1)-dimensional growing surfaces [19], the Darcy model of fluid propagation in the porous media [20] and the three-state Potts model [21]. Many aspects of this model are known, ranging from its Fokker-Planck equation [22], to its relation to the other models like the Coulomb gases [2], and also many statistical features (SLE predictions) of the the random curves are kown, such as the left passage probability [4], the fractal dimension, and the Cardy's crossing probability [2].…”
Section: Introductionmentioning
confidence: 99%